PLASTICITY AND ADAPTABILITY OF RED BEET ACCESSIONS IN VERTICAL ZONATION OF CENTRAL PRE-CAUCASIAN REGION - M. Sh. Gaplaev (Овощи России, 2017)
The problem to choose and use ecologically plasticiable cultivar accessions is one of the most important stage of the program for adaptive vegetable production. The right decision of the problem leads to rational utilization of material and natural resources, decreasing the expenses and charges. For successful development of vegetable breeding the cultivar adaptive specifications is necessary to know. Vertical zonation along with hydrothermal condition had an essential effect on yield of red beet. Not being depended on maturity type of cultivar accession their yield increased by 1.9-3.2 t/ha successively from plains towards mountain zone, corresponding to pre-mountain and mountainous regions in Chechen Republic. On average, for tree-year study the highest yield was 45.8 and 45.1 t/ha in cultivars ‘Bona’ and ‘Tsilindra’ respectively, not being depended on the zone of cultivation. The cultivars ‘Donskaya Ploskaya’ (flat), and ‘Odnorostkovaya’ were sources of ecological resistance, while the cultivars ‘Boltardy’ and ‘Detroit’ were sources of productivity. The cultivars ‘Boltardy’ and ‘Gribovskaya Ploskaya’ that had been responsive on regulated environmental factors and resistant to unregulated environmental factors were of multipurpose usage and intensive-cultivation type. The ‘Bordo 237’, Dvusemiyannaya TCKHA’, ‘Odnorostkovaya’ and ‘Tsilindra’ were distinguished from other by accumulation of dry matter and total sugars in all zones of cultivation. On cultivation zone change from steppe towards pre-mountain and mountainous region, the tendency was revealed that dry matter, total sugars and vitamin C content had increased, while the nitrate content had only depended on cultivar features.